The Histone Deacetylase Inhibitor Trichostatin A Promotes Totipotency in the Male Gametophyte. Issue 1 (24th January 2014) - Li, Hui; Soriano, Mercedes; Cordewener, Jan; Muiño, Jose M.; Riksen, Tjitske; Fukuoka, Hiroyuki; Angenent, Gerco C.; Boutilier, Kim
Abstract : Immature pollen of many species can be reprogrammed to form haploid embryos in vitro in response to a stress treatment. This work, in Brassica napus and Arabidopsis thaliana, showed that this stress-induced switch in developmental pathways relies on the inhibition of histone deacetylase activity. Abstract: The haploid male gametophyte, the pollen grain, is a terminally differentiated structure whose function ends at fertilization. Plant breeding and propagation widely use haploid embryo production from in vitro–cultured male gametophytes, but this technique remains poorly understood at the mechanistic level. Here, we show that histone deacetylases (HDACs ) regulate the switch to haploid embryogenesis. Blocking HDAC activity with trichostatin A (TSA ) in cultured male gametophytes of Brassica napus leads to a large increase in the proportion of cells that switch from pollen to embryogenic growth. Embryogenic growth is enhanced by, but not dependent on, the high-temperature stress that is normally used to induce haploid embryogenesis in B. napus . The male gametophyte of Arabidopsis thaliana, which is recalcitrant to haploid embryo development in culture, also forms embryogenic cell clusters after TSA treatment. Genetic analysis suggests that the HDAC protein HDA17 plays a role in this process. TSA treatment of male gametophytes is associated with the hyperacetylation of histones H3 and H4. We propose that the totipotency of the male gametophyte is kept in check by an HDAC -dependent mechanism and that the stress treatments used to induce haploid embryo development in culture impinge on this HDAC -dependent pathway.